Identifying potential urban focal points using multiple centrality assessment (MCA): Da Nang’s center as a case study - Ngoc Hong Nguyen; Trung Xuan Nguyen (Tạp chí Khoa học và Công nghệ)
Conventionally, identifying urban focal points is primarily based on subjective and intuitive evaluations. This paper aims to establish an objective method for identifying urban focal points by applying Multiple Centrality Assessment (MCA), a spatial network analysis tool. The authors calculate Betweenness, Straightness, and Closeness values within the urban street network and combine these metrics to generate a composite value, thereby identifying urban focal points in terms of connectivity and accessibility. This combined value is used to create maps of focal points and focal clusters, providing a scientific approach in this practice of urban design. The paper uses Da Nang City as a case study. The study’s results offer an evident-based approach in proposing urban focal points in urban design and planning.